VCAM-1 predicts poor prognosis and modulates immune infiltration in gastric cancer: a TCGA-based bioinformatics study - Wu, Cheng; Liu, Yungeng; Liu, Chuanyuan; Fang, Chuanfa (Frontiers in Genetics, 2025)
BackgroundGastric cancer (GC) is a leading cause of cancer-related mortality; however, biomarkers predicting its immunotherapy resistance remain scarce. Vascular cell adhesion molecule (VCAM)-1, an immune cell adhesion mediator, is implicated in tumor progression; however, its prognostic and immunomodulatory roles in GC remain unclear.MethodsIn this study, we analyzed VCAM-1 expression and its clinical relevance in GC using RNA-sequencing data from The Cancer Genome Atlas. Differential gene analysis, gene set enrichment analysis (GSEA), and single-sample GSEA were used to identify the underlying pathways and immune infiltration patterns. Validation was performed via Cox regression, receiver operating characteristic, and immunohistochemical (Human Protein Atlas database) analyses.ResultsVCAM-1 expression levels were significantly upregulated in the GC tissues (p < 0.001) and correlated with advanced T stage (p = 0.046), N stage (p = 0.047), and poor overall survival (hazard ratio = 1.54; p = 0.046). GSEA linked VCAM-1 expression to various immune pathways (e.g., interleukin-17 signaling), and single-sample GSEA revealed its positive associations with the Th1, cytotoxic, and CD8+ T cell proportions (p < 0.05) and inverse correlation with the Th17 cell proportion. Immunohistochemistry revealed elevated VCAM-1 protein levels in the tumors.ConclusionVCAM-1 is a novel prognostic biomarker driving immunosuppressive microenvironmental remodeling in GC. Furthermore, its dual roles in immune regulation highlight its potential to optimize GC immunotherapy.